The Implementation of Sharia Principle at Klaten Islamic General Based on Fatwa DSN MUI NO 107/DSN-MUI/X/2016 - Lahuri, Setiawan bin; Firmansyah, Rania Hasasaki; Zuhroh, Ainun Amalia (Universitas Siliwangi, 2025)
Introduction to The Problem: The number of Islamic hospitals in Indonesia is quite large, but unfortunately, the number of hospitals that have Sharia status is still minimal. Klaten Islamic General Hospital is one of the Islamic hospitals certified as Sharia since 2019.Purpose/Objective Study: This research aims to determine the Implementation of Sharia principles in Klaten Islamic General based on DSN MUI Fatwa N0 107 of 2016.Design/Methodology/Approach: The research method used qualitative with a field study approach. This research collected data through in-depth interviews with health workers, employees, and Klaten Islamic General Hospital administrators. The analysis was carried out based on DSN MUI Fatwa No. 107 of 2016 concerning Sharia hospital guidelines to described the implementation of Sharia principles in Klaten Islamic General Hospital. The results showed that Klaten Islamic General Hospital has consistently applied Sharia principles in contracts, services, medicines, food and beverages, and fund management. Klaten Islamic General Hospital has generally implemented Sharia principles using four mandatory provisions to organize hospitals based on Sharia principles listed in DSN-MUI Fatwa No. 107/DSN-MUI/X/2016. In addition, Klaten Islamic General Hospital has several advantages over other Sharia hospitals, including food in halal-certified canteens and Sharia laundry.Findings: This study provides recommendations to the Klaten Islamic General Hospital to improve the services for patients. Furthermore, the community or patients choose a Sharia hospital that creates the balancing between hospitality and spiritual needs of patients.Paper Type: Research Article